The role of Indigenous Health Workers in ear health screening programs: a scoping review protocol - Brianna Poirier; Leanne Quirino; Michelle Allen; Roland Wilson; Stephens, Jacqueline (Flinders University, 2021)
Introduction: Rates of ear disease and consequent hearing loss are greater for First Nations children than for their non-Indigenous counterparts in Australia, Canada, the United States, and New Zealand. While the First Nations health workforce is recognised as being vital to the provision of culturally appropriate health care to First Nations peoples and communities, there is a lack of information about Indigenous Health Workers’ role in ear health screening programs. A preliminary search of MEDLINE, the Cochrane Database of Systematic Reviews and JBI Evidence Synthesis was conducted and no current or underway systematic reviews or scoping reviews on the topic were identified. Review question: What are IHWs’ perspectives about their roles, involvement, and training in the provision of ear health screening programs for First Nations peoples and communities in Australia, Canada, New Zealand, and the United States?